Critical Race Theory as a Lens Developed in Preservice Early Childhood Education Teacher Training Programs - Khodarahmi, Negar; Ford, Laurie (Journal of Childhood Studies, 2025)
There is a pervasive false belief that young children are colour-blind and “racially innocent” and exist in “race neutral” spaces. A long-held belief in a universal model of child development underestimates children’s ability to engage with complex topics, and racialized students’ lived experiences are dismissed. Failing to engage in these discussions, educators could unknowingly neglect the needs of their students and fail to help children develop their cultural competencies. The purpose of this paper is to highlight the ways in which critical race theory can offer a lens through which to challenge the dominant ideology and sustained inequity in early childhood education and educational systems.